2001
DOI: 10.2134/agronj2001.93137x
|View full text |Cite
|
Sign up to set email alerts
|

Weed Suppression by Release of Isothiocyanates from Turnip‐Rape Mulch

Abstract: wick et al., 1983). Living plants do not actively release high amounts of ITCs (Bö rner, 1961), because glucosi-The allelopathic potential of isothiocyanates (ITC) released by nolates are located in the vacuole and myrosinase is turnip-rape mulch [Brassica rapa (Rapifera Group)-Brassica napus L.] was evaluated. Six different ITCs were identified from chopped bound to the cell wall (Bjö rkman, 1976). As long as this turnip-rape by HPLC-DAD/HPLC-MS. All plant parts contained separation exists, there is only a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
189
0
14

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(215 citation statements)
references
References 20 publications
12
189
0
14
Order By: Relevance
“…A família Brassicaceae caracteriza-se por produzir glucosinolatos (Oerlemans et al, 2006), que, quando decompostos, transformam-se em isotiocianatos e tiocianatos (Eberlein et al, 1998). Essas substâncias podem, em baixas concentrações, atrasar a germinação e, em altas concentrações, penetrar nas sementes, tornando-as inviáveis (Petersen et al, 2001). …”
Section: Resultsunclassified
“…A família Brassicaceae caracteriza-se por produzir glucosinolatos (Oerlemans et al, 2006), que, quando decompostos, transformam-se em isotiocianatos e tiocianatos (Eberlein et al, 1998). Essas substâncias podem, em baixas concentrações, atrasar a germinação e, em altas concentrações, penetrar nas sementes, tornando-as inviáveis (Petersen et al, 2001). …”
Section: Resultsunclassified
“…For example, in aqueous extracts, arylisothiocyanate from domesticated winter B. rapa was the most potent inhibitors of germination in several species [T. aestivum L., Sonchus asper (L.) Hill, Matricaria inodora L., Amaranthus hybridus L., Echinochloa crus-galli (L.) Beauv., Alopecurus myosuroides Huds.] (Petersen et al 2001), while allyl-isothiocyanate and methyl-isothiocyanate were the most active allelopathic compounds in the volatile phase and consistently provided I 50 values (the concentration at which 50% of germination is inhibited) for germination of soybean [Glycine max (L.) Merr. ], corn (Zea mays L.), canola, alfalfa (Medicago sativa L.), dandelion (Taraxacum officinalis Weber), cucumber (Cucumis sativus L.), and wheat (Triticum aestivum L.) at concentrations below 1 ppm.…”
mentioning
confidence: 94%
“…Leachates from domesticated spring B. napus residue were more potent to stinkweed (Thlaspi arvense L.), flixweed (Descurainia sophia L.), and downy brome (Bromus tectorum L.) than to winter wheat (Triticum aestivum L.), suggesting the possibility of selective management of these weeds in notill, direct-seeded farming systems in Alberta (Moyer and Huang 1997). Water soluble and volatile isothiocyanates have been identified as allelopathic compounds (Vaughn and Boydston 1997;Petersen et al 2001). Potency of isothiosyanates is dependent on form at each phase.…”
mentioning
confidence: 99%
“…Exposure to the volatiles from the leaves delayed seed germination and decreased subsequent growth of these species. Peterson et al (2001) reported that volatile isothiocyanates, one of the degradation products of glucosinolates, suppressed weed germination after the incorporation of turnip-rapeseed green mulch into the soil. They reported that the isothiocyanate produced in large amounts by the mulch suppressed weed germination.…”
mentioning
confidence: 99%